Balloon Guide Catheter Is Beneficial in Endovascular Treatment Regardless of Mechanical Recanalization Modality. Issue 6 (June 2019) - Baek, Jang-Hyun; Kim, Byung Moon; Kang, Dong-Hun; Heo, Ji Hoe; Nam, Hyo Suk; Kim, Young Dae; Hwang, Yang-Ha; Kim, Yong-Won; Kim, Yong-Sun; Kim, Dong Joon; Kwak, Hyo Sung; Roh, Hong Gee; et al.
Abstract : Background and Purpose—: Based on its mechanism, the use of balloon guide catheters (BGCs) may be beneficial during endovascular treatment, regardless of the type of mechanical recanalization modality used—stent retriever thrombectomy or thrombaspiration. We evaluated whether the use of BGCs can be beneficial regardless of the first-line mechanical endovascular modality used. Methods—: We retrospectively reviewed consecutive acute stroke patients who underwent stent retriever thrombectomy or thrombaspiration from the prospectively maintained registries of 17 stroke centers nationwide. Patients were assigned to the BGC or non-BGC group based on the use of BGCs during procedures. Endovascular and clinical outcomes were compared between the BGC and non-BGC groups. To adjust the influence of the type of first-line endovascular modality on successful recanalization and favorable outcome, multivariable analyses were also performed. Results—: This study included a total of 955 patients. Stent retriever thrombectomy was used as the first-line modality in 526 patients (55.1%) and thrombaspiration in 429 (44.9%). BGC was used in 516 patients (54.0%; 61.2% of stent retriever thrombectomy patients; 45.2% of thrombaspiration patients). The successful recanalization rate was significantly higher in the BGC group compared with the non-BGC group (86.8% versus 74.7%, respectively; P <0.001). Furthermore, the first-pass recanalization rate was more frequent (37.0% versus 14.1%; P <0.001), and the number of device passes was fewer in the BGC group (2.5±1.9 versus 3.3±2.1; P <0.001). The procedural time was also shorter in the BGC group (54.3±27.4 versus 67.6±38.2; P <0.001). The use of BGC was an independent factor for successful recanalization (odds ratio, 2.18; 95% CI, 1.54–3.10; P <0.001) irrespective of the type of first-line endovascular modality used. The use of BGC was also an independent factor for a favorable outcome (odds ratio, 1.40; 95% CI, 1.02–1.92; P =0.038) irrespective of the type of first-line endovascular modality used. Conclusions—: Regardless of the first-line mechanical endovascular modality used, the use of BGC in endovascular treatment was beneficial in terms of both recanalization success and functional outcome. Abstract : Supplemental Digital Content is available in the text.